Digital well-being among Generation Z employees in Indonesia - Margaretha Sabda Djaja; Zamralita Zamralita; Ismoro Reza Prima Putra (Priviet Social Sciences Journal, 2026)
Digital transformation has intensified the use of digital technologies in the workplace, raising concerns about employee well-being, particularly among Generation Z employees who are highly familiar with these technologies. This study aims to examine the level of digital well-being among Generation Z employees in digitalized work environments and investigate differences based on the duration of digital technology use. A quantitative, non-experimental survey design was employed. The participants consisted of 237 Generation Z employees in Indonesia aged 18-27 years, with a minimum of one year of work experience. The results indicated that the data were normally distributed and revealed significant differences in digital well-being levels based on the duration of digital technology use. Employees who reported longer durations of digital technology use tended to experience higher digital well-being. In contrast, demographic characteristics such as gender, educational level, work experience, and job position did not show significant differences in terms of digital well-being. These findings suggest that digital well-being is more strongly influenced by the patterns and duration of technology use than by demographic factors. This study concludes that the duration of digital technology use plays an important role in shaping the digital well-being of Generation Z employees. When managed adaptively and in a balanced manner, intensive technology use can support employees’ psychological and emotional well-being. Therefore, organizations and employees should promote healthy digital practices to sustain digital well-being in the digital work era.